Kesendirian (Solitude) sebagai Pengalaman Positif di Masa Pembatasan Sosial - Milda Longgeita Pinem (Jurnal Filsafat Indonesia, 2022)
The purpose of this article is to discuss solitude during the social distancing era caused by theCovid-19 pandemic. Various studies showed that the pandemic had an impact on aspects ofhuman life such as health, economy, social, and education. Aside from those various aspects,one of the life changes that many people experienced during pandemic is social distancing or physical distancing. People were forced to live in solitude in the social distancing era. In general,solitude is an uninteresting topic to discuss. The situation is even more viewed negatively andassociated with loneliness, sadness, and even helplessness. In contrast to the negative view, thisarticle aims to clarify solitude from a more positive standpoint. This study uses a qualitativemethod with a literature study approach. The data sources come from various literatures thatintersect social sciences, philosophy and spirituality, particularly those that address the theme of solitude. Three findings were identified and analyzed based on the various literature. First,solitude encourages individuals to increasingly recognize themselves. Second, solitude createsa space of freedom for humans, particularly in the context of social relations. Third, solitude bringspeople closer to nature. This article closes with a conclusion about the importance of practicingsolitude in certain situations, even outside the context of a pandemic